Gene B-5 in cotton confers high and broad resistance to bacterial blight and conditions high amounts of sesquiterpenoid phytoalexins - Essenberg, Margaret; McNally, Kenneth L.; Bayles, Melanie B.; Pierce, Margaret L.; Hall, Judy A.; Kuss, Christine R.; Shevell, Judith L.; Verhalen, Laval M. (Scientific Societies, 2023)
Bacterial blight resistance gene B5 has received little attention since it was first described in 1950. A near-isogenic line (NIL) of Gossypium hirsutum cotton, Ac B5, was generated in an otherwise bacterial-blight-susceptible ‘Acala 44’ background. The introgressed locus B5 in Ac B5 conferred strong and broad-spectrum resistance to bacterial blight. Segregation patterns of test crosses under Oklahoma field conditions indicated that Ac B5 is likely homozygous for resistance at two loci with partial dominance gene action. In controlled-environment conditions, two of the four copies of B5 were required for effective resistance. Contrary to expectations of gene-for-gene theory, Ac B5 conferred high resistance toward isogenic strains of Xanthomonas citri subsp. malvacearum carrying cloned avirulence genes avrB4, avrb7, avrBIn, avrB101, and avrB102, respectively, and weaker resistance toward the strain carrying cloned avrb6. The hypothesis that each B gene, in the absence of a polygenic complex, triggers sesquiterpenoid phytoalexin production was tested by measurement of cadalene and lacinilene phytoalexins during resistant responses in five NILs carrying different B genes, four other lines carrying multiple resistance genes, as well as susceptible Ac44E. Phytoalexin production was an obvious, but variable, response in all nine resistant lines. Ac B5 accumulated an order of magnitude more of all four phytoalexins than any of the other resistant NILs. Its total levels were comparable to those detected in OK1.2, a highly resistant line that possesses several B genes in a polygenic background.